Hip Arthroscopic Reduction and Fixation for Adolescent Acetabular Posterior Wall Fracture: A Case Report - Rong‐mao Shi; Li‐bo Yuan; Chao‐jun Tan; An‐xu Li; Xiong Qiu; Bing Yang; Hong‐bo Tan (Orthopaedic Surgery, 2021)
Background Posterior wall fracture is the most common type of acetabular fracture, the traditional open reduction and fixation through the Kocher–Langenbeck approach required a large incision and extensive muscle and soft tissue dissection, resulting in more blood loss, more complications and delayed recovery after the operation. Hip arthroscopy has been widely used in clinical practice but rarely reported in acetabular fractures. Case Presentation We present the case of a 14‐year‐old boy with acetabular posterior wall fracture who was treated with hip arthroscopy reduction and fixation using anchors. He began to walk with partial weight‐bearing assisted by double crutches, and returned to school with crutches at 3 days after surgery. Although hip arthroscopy is technically more demanding, it’s an optimal choice for selected patients of acetabular fracture with the advantages of less invasive and faster postoperative recovery.